Simulation of an M 7.1 Lateral Fault Coastal Earthquake: A Plausible Scenario for Seismic Hazard Assessment in Michoacan, Mexico - Ricardo Vázquez Rosas; Jorge Aguirre González; Gerardo León Soto; José Antonio Hernández Servín (Applied Sciences)
The effects of a synthetic M 7.1 strike lateral earthquake are evaluated at five sites in Michoacan state, western Mexico. In this work, the ground motion simulation was applied using the empirical Green’s function method proposed by Irikura (1986) by scaling the recordings of an M 5.1 left-lateral event to a hypothetical M 7.1 event assuming the same source mechanism. An M 4.3 was used as a Green’s function to generate an M 5.1 synthetic earthquake. Comparing the observed and synthetic M 5.1 earthquake, parameters were adjusted in order to scale the M 7.1 earthquake. Seven scenarios were tested for which the corresponding PGA and PGV were calculated. The results show that the maximum intensities at each station depend on the proposed rupture starting point. The highest Peak Ground Acceleration was 74.1 cm/s2 corresponding to an intensity MMI of V at FMIR station located 60 km from the epicenter. The synthetic results constitute a useful input for seismic hazard studies in a state with poor instrumental deployment, such as Michoacan, and for technical standards for earthquake design that could be considered in the corresponding construction regulations.